Immunogenicity and safety of influenza vaccination in patients with juvenile idiopathic arthritis on biological therapy using the microneutralization assay - M. S. Camacho-Lovillo; A. Bulnes-Ramos; W. Goycochea-Valdivia; L. Fernández-Silveira; E. Núñez-Cuadros; O. Neth; P. Pérez-Romero (BMC, 2017)
Abstract Background Seasonal influenza virus vaccination should be considered in all pediatric patients with rheumatic diseases. Few studies have addressed influenza vaccination safety and efficacy in this group. We aim to prospectively evaluate immunogenicity and safety of the trivalent inactivated influenza vaccine including A/H1N1, A/H3N2 and B strains in children with juvenile idiopathic arthritis (JIA) receiving biological therapy. Methods Thirty-five children diagnosed with JIA and 6 healthy siblings were included. Serum samples were collected prior to, 4-8 weeks and one year after vaccination. Microneutralization assays were used to determine neutralizing antibody titers. The type and duration of therapy were analyzed to determine its effect on vaccine response. Clinical data of the participants were collected throughout the study including severe adverse events (SAE) and adverse events following immunization (AEFI). Results Twenty-five patients (74.3%) received biological treatment for JIA; anti TNF-α was prescribed in 15, anti IL-1 receptor in 4 and anti IL-6 receptor therapy in 6 children. The seroprotection rate 4-8 weeks after vaccination in the JIA group was 96% for influenza A/(H1N1)pdm and influenza A/H3N2, and 88% for influenza B. No differences were found in GMT, seroprotection and seroconversion rates for the three influenza strains between the control group and patients receiving biological therapy. Furthermore, long-term seroprotection at 12 months after vaccination was similar in patients receiving either biological or non-biological treatments. No SAEs were observed. Conclusions In this study, influenza vaccination was safe and immunogenic in children with JIA receiving biological therapy.